2014
DOI: 10.1589/jpts.26.363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Direct Current Stimulation of Function in Patients with Stroke

Abstract: [Purpose] The purpose of this study was to determine the effect of transcranial direct current stimulation (tDCS) on the upper limb of function of patients with post-stroke hemiplegia. [Subjects] Twenty subjects were randomly allocated to either the upper tDCS group or the functional training group, with 10 subjects in each group. [Methods] The two groups received functional training for thirty minutes a day, five days a week for four weeks. The tDCS group additionally received tDCS for 20 minutes. The outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 19 publications
0
43
1
1
Order By: Relevance
“…tDCS is used to stimulate the cerebral cortex directly, in order to control the activities of the cortex. tDCS can impact the function of a specific neural structure and augment treatment effects during the rehabilitation process through brain stimulation2 ) . Since tDCS is highly portable and safe, as well as economical, it can be used conveniently for the purposes of research and treatment3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…tDCS is used to stimulate the cerebral cortex directly, in order to control the activities of the cortex. tDCS can impact the function of a specific neural structure and augment treatment effects during the rehabilitation process through brain stimulation2 ) . Since tDCS is highly portable and safe, as well as economical, it can be used conveniently for the purposes of research and treatment3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, transcranial direct current stimu-lation (tDCS), a form of non-invasive brain stimulation that modulates cortical excitability, has been considered as a possible adjunct to conventional physical therapy aimed at post-stroke motor recovery (Cha et al, 2014;Kim et al, 2010;Lindenberg et al, 2010;Jayaram and Stinear, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…LF-TMS over the unaffected hemisphere may be more beneficial than rTMS over the affected hemisphere. Most of the individual studies reported clinical improvement of upper-limb motor disorder more commonly found in patients with subcortical lesions, when the rTMS intervention was coupled with traditional rehabilitation, and when the stimulation was applied over the nonlesioned hemisphere [17].…”
Section: Tdcs Study In Post-stroke and Parkinson's Diseasementioning
confidence: 99%
“…In one study, 38 patients with post stroke hemiparesis, LF-rTMS (20 min) was combined with physical exercise during 15 days of hospitalization [17] and scores of the TUG test, dynamic gait index and the functional balance scale were significantly improved.…”
Section: Combined Approachesmentioning
confidence: 99%